2020
DOI: 10.1002/aocs.12462
|View full text |Cite
|
Sign up to set email alerts
|

Castor Epoxy Fatty Acid Alkyl Ester Estolides as Bioplasticizers for Poly(Vinyl Chloride)

Abstract: Epoxy fatty acid alkyl ester estolides were synthesized from castor oil to be used as biobased plasticizers for poly(vinyl chloride) (PVC) as a safer replacement for phthalate plasticizers. Initially, castor oil was transesterified with methanol or n‐butanol to quantitatively yield castor fatty acid alkyl esters. Acetylation of hydroxyl function with acetic anhydride led to the formation of estolide. The unsaturation was epoxidized, resulting in a bifunctional epoxy fatty acid alkyl ester estolide. The bioplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…PVC, in its native state, is a rigid polymer with a somewhat restricted scope of use. However, when subjected to specific additives, such as plasticizers, PVC undergoes a transformation, becoming flexible and broadening its range of applications 3 . Plasticizers, typically composed of relatively small molecules, are introduced into polymer materials to enhance the processability, flexibility, or diffusibility of the polymer matrix 4 .…”
Section: Introductionmentioning
confidence: 99%
“…PVC, in its native state, is a rigid polymer with a somewhat restricted scope of use. However, when subjected to specific additives, such as plasticizers, PVC undergoes a transformation, becoming flexible and broadening its range of applications 3 . Plasticizers, typically composed of relatively small molecules, are introduced into polymer materials to enhance the processability, flexibility, or diffusibility of the polymer matrix 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Plasticizers can be inserted into polymer molecules to increase the distance between polymer molecules and reduce the intermolecular force, which can greatly improve the processability of PVC and make it have good weather resistance and mechanical properties. 16,23,[28][29][30][31][32] For a long time, the plasticizers used for PVC have mainly been phthalates, and the most widely used is dioctyl phthalate (DOP), 10,11,[33][34][35] but it is easy to migrate out and is toxic, which will affect the application performance of the product, and many animal experiments have shown that DOP is potentially carcinogenic, [36][37][38][39][40][41] and its application in most daily products has been banned in many countries. Therefore, the development of new non-toxic migration-resistant plasticizers has become a research hotspot.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] Chemicals derived from biomass resources are diverse in structure, widely sourced and sustainable, laying the foundation for their further industrialization. According to previous reports, many biobased plasticizers derived from biomass resources have been successfully prepared, such as vegetable oil derivatives (tung oil, palm oil, castor oil, soybean oil, citrus seed oil), [25][26][27][28][29] waste kitchen oil derivatives, 9,[30][31][32] tartrates, 11,33 malates, 34 vanillates, 35 glycerin derivatives 36,37 and so on. 4,38,39 Lactic acid is a renewable biomass feedstock that can be produced in large quantities from starchy crops.…”
mentioning
confidence: 99%